2012
DOI: 10.1371/journal.pgen.1002641
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Ancestry, Signatures of Natural Selection, and Genetic Association with Stature in Western African Pygmies

Abstract: African Pygmy groups show a distinctive pattern of phenotypic variation, including short stature, which is thought to reflect past adaptation to a tropical environment. Here, we analyze Illumina 1M SNP array data in three Western Pygmy populations from Cameroon and three neighboring Bantu-speaking agricultural populations with whom they have admixed. We infer genome-wide ancestry, scan for signals of positive selection, and perform targeted genetic association with measured height variation. We identify multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
132
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 119 publications
(152 citation statements)
references
References 81 publications
(129 reference statements)
11
132
1
1
Order By: Relevance
“…This confirms the suggestive associations found by a recent genome-wide study. 22 Interestingly, the SNPs identified here in the GHR and IGF1 genes have not been shown to be associated with height in large-scale genome-wide association studies. 57 Indeed, their frequency is low in the European population (CEU) from HapMap 56 (GHR rs4642376: 10.17%, rs1912107: 10.0%, rs2972419: 11.67% and IGF1 rs11831436: 5.83%).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…This confirms the suggestive associations found by a recent genome-wide study. 22 Interestingly, the SNPs identified here in the GHR and IGF1 genes have not been shown to be associated with height in large-scale genome-wide association studies. 57 Indeed, their frequency is low in the European population (CEU) from HapMap 56 (GHR rs4642376: 10.17%, rs1912107: 10.0%, rs2972419: 11.67% and IGF1 rs11831436: 5.83%).…”
Section: Discussionmentioning
confidence: 70%
“…[18][19][20][21] A recent genome-wide study has identified regions in the genome that might be involved in the difference in stature observed between pygmies from Cameroon and their non-pygmy neighbors, although this signal was not significant. 22 Some of these regions contain genes linked to the GH-IGF1 signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, 295 individuals were retained for subsequent analyses, including 216 unrelated individuals, 21 complete trios and 8 duos, totalling 266 unrelated samples. This data set was analysed in conjunction with genome-wide data from 11 additional African populations 26,29 , including 4 Western RHG populations (Baka, Bakola and Bezan of Cameroon, and Biaka of Central African Republic-CAR), 1 Eastern RHG population (Mbuti of the Democratic Republic of Congo) and 6 AGR relevant populations ( Fig. 1a; Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…We merged our genotyping data for 930,134 SNPs in 295 individuals with data for 221 additional samples, retrieved from previous studies 26,29 Table 1; dbGaP study accession: phs000449.v2.p1). We restricted the three data sets to the SNPs that were genotyped in all, yielding a total of 363,088 polymorphic SNPs in 516 individuals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation